The Inhibitory Action of Adsorbed Undiluted Plasma (normal or pathological) on the Thromboplastin Generation Test - Mayer, G; Mayer, S; Waitz, R (Thrombosis and Haemostasis, 1960)
In considering errors made during the search for a weak inhibitor of thromboplastin generation in a patient suffering from multiple myeloma, the authors recall the inhibitory action of adsorbed undiluted plasma added to a thromboplastin generation test. They stress the non-specificity of this inhibitory action which is common to all adsorbed plasma (normal, myelomatous or hemophilic) added undiluted to the test of Biggs and Douglas.